Dynamic Target Tracking with Integration of Communication and Coverage using Mobile Sensors - Hongbin Li (2009)
This paper presents a decentralized motion coordination algorithm for distributed sensing of dynamic noncooperative targets in a noisy environment by multiple cooperating mobile sensors. Mobile sensors, by nature, adjust their positions to increase the quality of sensing. In this case, we consider the existence of imperfect communications and limited sensing range. Connectivity and coverage constraints are also considered and included in the cost function that is used to drive the sensors so that information sharing among them as well as a certain degree of area coverage are maintained. The gradient-descent method is employed to minimize the global cost function. We examine the trade-offs in performance between sensing, communication and coverage. Several simulations are used to show the effectiveness of the proposed control approach and preliminary experimental results validate our tracking method.